Desistance and restorative justice: learning from success stories of Northern Ireland's Youth Justice Agency. Issue 3 (1st September 2016) - Marsh, Brendan; Maruna, Shadd
ABSTRACT: Although individual 'success stories' are often dismissed as anecdotal evidence in evaluating the work of criminal justice agencies, such individuals may have a great deal to teach those interested in improving justice interventions. This research explores the self-narratives of 24 young people who were formerly involved in restorative conferencing with the youth justice system in Northern Ireland (UK) to better understand the role that this work had (or did not have) on their efforts to desist from crime. These data suggest that the conferences that had the longest lasting impact were those in which the individual was confronted by a direct victim of personal violence. Conferences that did not involve direct victim input involved lecturing by police officers or that were conducted whilst the young person was intoxicated were largely dismissed by participants as lacking impact. Other aspects of restorative practice beyond conferencing, including reparation plans that involved drug-addiction treatment and other forms of counselling, were discussed more frequently as being central to the desistance process for interviewees. The most impactful aspects of youth justice involvement for interviewees were the human connections made with agency staff.